MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWA MELALUI PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) PADA KELAS V SDN SEMERU 1 TAHUN AJARAN 2024/2025 - Armanda, Rendi; Yani, Indri; Cynit Rahila Retyana, Cyntya; Ainun Ni'mah, Miftah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Education is a crucial effort to develop individual potential through a conducive learning environment. However, mathematics is often perceived as difficult and irrelevant due to its abstract nature. To address this, the Realistic Mathematics Education (RME) approach is utilized, aiming to connect mathematical concepts with students' real-world experiences. This study aims to investigate the effect of implementing RME on the conceptual understanding and learning outcomes of fifth-grade students at SDN Semeru 1. The research employs Classroom Action Research (CAR) following the Kemmis and McTaggart model in two cycles. The subjects consist of 34 students, and the object of study is the mathematics learning outcomes measured through pre-tests, post-test 1, and post-test 2. The results reveal an increase in the students’ average score from 75.33 (pre-test) to 86.71 (post-test 2), along with an improvement in mastery learning percentage from 64.71% to 94.12%. These findings demonstrate that the RME approach is effective in enhancing students’ conceptual understanding and mathematics learning outcomes by utilizing real-life contexts, providing intensive teacher guidance, and conducting structured discussions. The implementation of RME is expected to offer a contextual, enjoyable, and meaningful mathematics learning experience for students.